Chiral optical response of multifold fermions - Flicker, F; De Juan, F; Bradlyn, B; Morimoto, T; Vergniory, MG; Grushin, AG (American Physical Society, 2018)
Multifold fermions are generalizations of twofold degenerate Weyl fermions with three-, four-, six-, or eightfold degeneracies protected by crystal symmetries, of which only the last type is necessarily nonchiral. Their low-energy degrees of freedom can be described as emergent relativistic particles not present in the standard model of particle physics. We propose a range of experimental probes for multifold fermions in chiral symmetry groups based on the gyrotropic magnetic effect (GME) and the circular photogalvanic effect (CPGE). We find that, in contrast to Weyl fermions, multifold fermions can have zero Berry curvature yet a finite GME, leading to an enhanced response. The CPGE is quantized and independent of frequency provided that the frequency region at which it is probed defines closed optically activated momentum surfaces. We confirm the above properties by calculations in symmetry-restricted tight-binding models with realistic density functional theory parameters. We identify a range of previously unidentified ternary compounds able to exhibit chiral multifold fermions of all types (including a range of materials in the families AsBaPt and Gd3 Cl3 C), and provide specific predictions for the known multifold material RhSi.